Analisis Sentimen pada Ekspedisi Kurir Online di Indonesia Menggunakan Algoritma Naive Bayes - Kurniawan, Heri; Miftakhurahmat, Moh. Aulia; Enri, Ultach (VISA: Journal of Vision and Ideas, 2024)
This journal focuses on sentiment analysis of four popular online courier expeditions in Indonesia, namely JNT, JNE, Shoope Express, and Anteraja. The purpose of this research is to understand the opinions and responses of users towards the online courier expedition service. The research was conducted using the sentiment analysis method, which utilizes data from user reviews contained in each online courier application on the Playstore platform. In this study, the Naive Bayes algorithm is used to perform sentiment analysis. This algorithm was chosen with the aim of producing higher accuracy results in determining positive and negative sentiments from user reviews. By using this method, this research hopes to provide a deeper understanding of the perceptions and experiences of users of the online courier service under study. The results of the study show that there are variations in user sentiment for each online courier expedition. User reviews include aspects of satisfaction with service, desired complaints, and problems that often arise when using the online courier application. These findings provide valuable insights for online courier service providers, as it can help them improve service quality and customer satisfaction. By understanding user opinions and feedback, online courier service providers can identify deficiencies in their services and make necessary improvements.